No Effect of High-Dose Vitamin D Supplementation on Glycemic Status or Cardiovascular Risk Factors in Subjects With Prediabetes - Sollid, Stina Therese; Hutchinson, Moira Y.S.; Fuskevåg, Ole M.; Figenschau, Yngve; Joakimsen, Ragnar M.; Schirmer, Henrik; Njølstad, Inger; Svartberg, Johan; Kamycheva, Elena; Jorde, Rolf (Diabetes care, 2014)
In observational studies, low serum 25-hydroxyvitamin D [25(OH)D] concentrations have been associated with insulin resistance and other risk factors for cardiovascular disease. We present 1-year data from an ongoing 5-year trial in 511 individuals with impaired fasting glucose (IFG) and/or impaired glucose tolerance (IGT) randomly assigned to 20,000 IU/week vitamin D3 or placebo. An oral glucose tolerance test was performed at baseline and after 1 year. Mean baseline serum 25(OH)D was 59.9 nmol/L and 61.1 nmol/L in the vitamin D and placebo groups, respectively, and increased by 45.8 nmol/L and 3.4 nmol/L, respectively. With adjustment for baseline concentrations, no differences in measures of glucose metabolism, insulin secretion or sensitivity, blood pressure, or hs-CRP were found after 1 year. There was a slight, but significant decrease in total and LDL cholesterol in the vitamin D group compared with the placebo group, but as there was also a decrease in HDL cholesterol, the change in the total/HDL cholesterol ratio did not differ significantly. Only analyzing subjects with 25(OH)D <50 nmol/L did not change the results. This study shows that vitamin D supplementation does not improve glycemic indices, blood pressure, or lipid status in subjects with IFG and/or IGT.